The Cambridge history of the Romance languages - Maiden, Martin, 1957-; Smith, John Charles, 1950-; Ledgeway, Adam. (Cambridge : Cambridge University Press, 2011)
'This Cambridge History is the most comprehensive survey of the history of the Romance languages ever published in English. It engages with new and original topics that reflect wider-ranging comparative concerns, such as the relation between diachrony and synchrony, morphosyntactic typology, pragmatic change, the structure of written Romance, and lexical stability. Volume I is organized around the two key recurrent themes of persistence (structural inheritance and continuity from Latin) and innovation (structural change and loss in Romance). An important and novel aspect of the volume is that it accords persistence in Romance a focus in its own right rather than treating it simply as the background to the study of change. In addition, it explores the patterns of innovation (including loss) at all linguistic levels. The result is a rich structural history which marries together data and theory to produce new perspectives on the structural evolution of the Romance languages'--
'This Cambridge History of the Romance Languages stands on the shoulders of giants. A glance at the list of bibliographical references in these volumes should suffice to give some idea of the enormous body of descriptive and interpretative literature on the history of the Romance languages, both from the point of view of their structural evolution (the main focus of this volume) and with regard to the contexts in which they have emerged as distinct'languages', and gained or lost speakers and territory, and come into contact with other languages (the focus of the second volume). This profusion of scholarship, adopting a multiplicity of approaches (synchronic, diachronic, microscopic, macroscopic) has more than once provided material for major, indeed monumental, comparative-historical synopses (e.g., Meyer-Lubke (1890-1902), Lausberg (1956-62), or the massively detailed and indispensable encyclopaedic works such as Holtus, Metzeltin and Schmitt (1988-96) and Ernst, Glessgen, Schmitt and Schweickard (2003-06))'--
Includes bibliographical references (p. 746-841) and index.
Keywords: Romance languages -- History